A Survey of Smoking and Estimating the Heavy Elements in Some Types of Cigarettes and Their Health Implications (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
The aim of this study was to measure the concentration of some heavy metals (Iron, copper, zinc, chromium, manganese, cobalt, lead, nickel) in five types of cigarettes (Marlboro, Rothmans, LM, Sports, Karela) in some of aden govemorate markets_ Sebha, at arate of three samples of each type, the Atomic Absorption Spectrophotometer technique was used to determine heavy metals. The results showed a significant increase in the concentration of heavy metals in types of cigarettes at probability of (P
Keywords: Cigarettes; Heavy Metals